The air gap effect on the fire resistance of composite slab with steel deck - Piloto, P.A.G. (2020)
The fire resistance of composite slabs with steel deck may be defined by experimental tests or using simple calculation methods available in standards, such as EN1994-1-2. The composite slab is made by a concrete topping cast on the top surface of a steel deck, presenting a combination of two different materials (steel and concrete). This work presents the results and the validation of a two dimensional finite element model, used for comparison with experimental results developed by the authors. Results are also compared with the simple calculation method of EN1994-1-2, which seems to be unsafe. The numerical model considers perfect contact between materials, but investigates the effect of the air gap between the concrete slab and the steel deck. The existence of the air gap is usually justified by different expansion coefficients and by the thermal bowing caused by the thermal gradient across the thickness, which leads to the separation of both materials during experimental tests.